(untitled) (Agricultural Engineering, 2019)
The paper presents results of the research on traction properties of two tractor tyres used on two agricultural grounds. The first ground was a stubble and the second one cropland. The investigated tyres had the same structure (diagonal, with a traditional tyre tread but different external dimensions. The research was carried out in field conditions with the use of a stand aggregated with a farm tractor. Analysis covered traction efficiency, slide, towing power and power lost on the rolling resistance and wheel slide. Based on the obtained results it was concluded that on a ground with lower compaction, the values of power losses were higher and traction efficiency was lower. Moreover, it was proved that the value of the power lost for rolling resistance had a decisive impact on the values of traction efficiency.